Viral composition and context in metagenomes from biofilm and suspended growth municipal wastewater treatment plants. Issue 6 (14th August 2019) - Petrovich, Morgan L.; Ben Maamar, Sarah; Hartmann, Erica M.; Murphy, Brian T.; Poretsky, Rachel S.; Wells, George F.
Summary: Wastewater treatment plants (WWTPs) contain high density and diversity of viruses which can significantly impact microbial communities in aquatic systems. While previous studies have investigated viruses in WWTP samples that have been specifically concentrated for viruses and filtered to exclude bacteria, little is known about viral communities associated with bacterial communities throughout wastewater treatment systems. Additionally, differences in viral composition between attached and suspended growth wastewater treatment bioprocesses are not well characterized. Here, shotgun metagenomics was used to analyse wastewater and biomass from transects through two full‐scale WWTPs for viral composition and associations with bacterial hosts. One WWTP used a suspended growth activated sludge bioreactor and the other used a biofilm reactor (trickling filter). Myoviridae, Podoviridae and Siphoviridae were the dominant viral families throughout both WWTPs, which are all from the order Caudovirales . Beta diversity analysis of viral sequences showed that samples clustered significantly both by plant and by specific sampling location. For each WWTP, the overall bacterial community structure was significantly different than community structure of bacterial taxa associated with viral sequences. These findings highlight viral community composition in transects through different WWTPs and provide context for dsDNA viral sequences in bacterial communities from these systems. Abstract : Shotgun metagenomics was used to analyze wastewater and biomass from transects through two full‐scale wastewater treatment plants (WWTPs) for viral composition and associations with bacterial hosts. Myoviridae, Podoviridae, and Siphoviridae were the dominant viral families throughout both WWTPs, which are all from the order Caudovirales . Beta diversity analysis of viral sequences showed that samples clustered significantly both by plant and by specific sampling location, and for each WWTP, the overall bacterial community structure was significantly different than community structure of bacterial taxa associated with viral sequences.